Enzyme-mediated binding of tyrosine to brome-mosaic-virus ribonucleic acid - Hall, T. C. (1972)
Incubation of tyrosine with the RNA from brome-mosaic-virus under conditions favourable for aminoacylation of tRNA resulted in binding of tyrosine to the viral RNA. Sucrose-density-gradient centrifugation showed that tyrosine binds to three and probably to all four of the viral RNA components. The bound amino acid was readily released in mild alkaline solutions. Of 20 amino acids tested, only tyrosine was found to bind. The maximum extent of binding observed was 0.58mol of tyrosine/mol of brome-mosaic-virus RNA.